The 21st century organization reinventing through reengineering - Bennis, Warren G. (Warren Bennis executive briefing series, 1997)
With this book, two distinguished experts present a proven five-phase process for making an organization leaner, more responsive, and more aware of it's customers' needs. Drawing on real-life change iniatives undertaken at Motorola, General Electric, Hewlett-Packard and other industry leaders, Bennis and Mische demystify the process of reinventing a company and address many questions critical to the success of comprehensive change efforts. Through trAnd analysis, case study examples, and facts lists--all presented in an easy-to-absorb SuperReading format--The 21st Century Organization examines the economic, quality control, and productivity issues associated with organizational restructuring and demonstrates how each will impact a company's ability to compete in the growing global marketplace.